(3JUeje h JfSjb GdeJfRgGJ h GdMOGFb GdYGeI Hjf GdeMdjI h GdYGdejI (B/ s - (3fSeI Mdei Cejf YHOGdMejO GdNTfs; (3TQja UHQi SYO GdOjf (B: s; (3WGQb YHOGddWja CHhGdYWG (B: s ((3GdbGgQI (B: s (3fSeI Mdei Cejf YHOGdMejO GdNTf (B: s, 2016)
(3fcef GdacQI GdCSGSjI ddOQGSI GdHMKjI ai JhSjY OGFQI GdacQ GdJNWjWji h GdJUejei GdVjb dacQI GdMOGFb h GdeJfRgGJ GdYGeI Ydi GdeSJhi GdeMdi(B: (3h eMGhdI ehGcHI GdacQ GdYGdei Ph GdfXQI GdTehdjI deKd gPg GdaQGZGJ GdYeQGfjI ef NdGd GdJWQb dJMdjd feGPL GdMOGFb h GdeJfRgGJ GdYGeI GdfGLMI Ydi GdeSJhi GdYGdei h eYQaI Gge fbGW GdbhI GdJi ecGfJgG ef GdhUhd dPdc h eMGhdI GNPgG ai GdGYJHGQ Ydi GdeSJhi GdeMdi(B. (3CgejI eMGhdI GdhUhd Gdi efgL JMdjdi ebJQM bGFe Ydi GdeYGjjQ GdYGdejI h GdYhGed GdCSGSjI dfLGM GdaQGZGJ GdYeQGfjI GdeJSJfHWI ef JMdjd ef (B100(3aQGZ YeQGfi Ydi eSJhi GdYGde HhGSWI efXeI Hi Hi Si GdCeQjcjI h HEecGfjI JWHjbI Ydi GdKdGK MOGFb eMd GdOQGSI HeOjfI GdbGgQI ef NdGd GdCSJHjGf h GdedGMXI h GdGSJbQGA ef bHd GdHGMK(B: (3Je GdhUhd Gdi efgL Jbjjei eQcH jecf GdGSJaGOI efg ai YedjI JUeje h JfSjb GdeJfRgGJ h GdMOGFb GdYGeI Ydi GdeSJhi GdeMdis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CSS JUeje GdeJfRgGJs; (3GdeYGjjQ GdJNWjWjI ddeJfRgGJs; (3JUfjaGJ GdMOGFbs